Luis Jerónimo de Oré and the poetry of his Indian Catholic Symbol (1598) - Chang-Rodríguez, Raquel (2019)
The Council of Trent promoted new ways to attract the neophytes to the Catholic faith. Following these directives, the Lima Church Councils in the Viceroyalty of Peru sponsored the publication of catechisms and grammars in native languages to help missionize the Andean population. Addressed to the indigenous groups and including numerous hymns in Quechua, Símbolo Católico Indiano (1598) by Luis Jerónimo de Oré, is representative of these efforts. This essay underscores the importance of Símbolo; it analyzes the themes of the hymns, their link to ancient Catholic practices, and how they acquire their singularity within the Peruvian context.